1972
DOI: 10.1901/jeab.1972.17-473
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF INCREMENTS IN NOISE INTENSITY BY MONKEYS1

Abstract: Monkeys were trained to detect 100-msec increments in the intensity of continuous white noise. A response on one of two bars was reinforced with some probability if it conformed to the presence or absence of the increment on that trial. Stimulus parameters of background intensity, increment size, and probability of increment presentation were varied, and response probabilities and latencies were recorded. The task was analogous to the "yes-no" task used in human psychophysics. Data analysis within the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Thus: log (;:) -log (;:) = 2 log d. (8) both animal and human subjects has shown that, while a subject's ability to discriminate between two stimuli remains constant, he may be induced to change his response probabilities in the presence of each of the two stimuli. In these studies, response bias (or criterion) has commonly been manipulated by varying the probability of presenting one of the two stimuli (e.g., Clopton, 1972;Elsmore, 1972;Galanter & Holman, 1967;Hume, 1974aHume, , 1974bHume & Irwin, 1974;Markowitz & Swets, 1967;Schulman & Greenberg, 1970;Swets, Tanner, & Birdsall, 1961;Terman & Terman, 1972). We have shown, however, that response bias is not a function of stimuluspresentation probability but, rather, is a function of the relative reinforcement frequency obtained for the choice responses.…”
Section: Bias and Signal Detection 373mentioning
confidence: 87%
“…Thus: log (;:) -log (;:) = 2 log d. (8) both animal and human subjects has shown that, while a subject's ability to discriminate between two stimuli remains constant, he may be induced to change his response probabilities in the presence of each of the two stimuli. In these studies, response bias (or criterion) has commonly been manipulated by varying the probability of presenting one of the two stimuli (e.g., Clopton, 1972;Elsmore, 1972;Galanter & Holman, 1967;Hume, 1974aHume, , 1974bHume & Irwin, 1974;Markowitz & Swets, 1967;Schulman & Greenberg, 1970;Swets, Tanner, & Birdsall, 1961;Terman & Terman, 1972). We have shown, however, that response bias is not a function of stimuluspresentation probability but, rather, is a function of the relative reinforcement frequency obtained for the choice responses.…”
Section: Bias and Signal Detection 373mentioning
confidence: 87%
“…When stimulus parameters are held constant, the detectability of a signal is typically found to remain constant and independent of changes in response bias. These findings have been obtained both with humans (Tanner & Swets, 1954;Swets, Tanner, & Birdsall, 1961;Green & Swets, 1966;Galanter & Holman, 1967, Markowitz & Swets, 1967Schulman & Greenberg, 1970) and with animals (Stubbs, 1968;Clopton, 1972;Elsmore, 1972;Terman & Terman, 1972;Hume & Irwin").…”
mentioning
confidence: 82%
“…The animals' sensitivity to increments in the intensity of random noise increased with the magnitude of the signal, and was independent of variations in response bias induced by varying either the signal probability or the relative payofffor correct responses (cf, Stubbs, 1968;Irwin & Terman, 1970;Terman, 1970;Clopton, 1972;Terman & Terman, 1972;Hume & Irwin, 1974;Hume, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Both ROC curves and their complementary bias functions have been obtained in stud ies with' animals *This research constituted a portion of a thesis submitted in partial fulfillment of the requirements for the PhD degree at the University of Auckland. The research was supported in part by grants from the New Zealand University Grants Committee and the Scientific Distribution Committee to R. J. by varying either the signal probability (Clopton, 1972;Elsmore, 1972;Hodos & Bonbright, 1972;Terman & Terman, 1972;Hume & Irwin, 1974;Hume, 1974) or the symmetry of the reinforcement contingencies (Stubbs, 1968;Hume, 1974). To date, only Terman and Terman (1972) have considered how response biases may vary as a joint function of the signal probability and the stimulus parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation